[Workers on a barge] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Caroni (1975) Limited workers on the barge which was used to clean up Caroni wells as the Caroni River.
Cataloger's title
Keywords: Barges -- Trinidad and Tobago; Wells -- Trinidad and Tobago; Wells--Cleaning -- Trinidad and Tobago; Caroni (1975) Limited